Competing Motivations in Grammar and Usage. - MacWhinney, Brian; Malʹchukov, A. L. (Andreĭ Lʹvovich); Moravcsik, Edith A. (Oxford linguistics., 2014)
This volume examines the conflicting factors that shape the content and form of grammatical rules in language, which speakers and addressees need to contend with when expressing themselves and when trying to comprehend messages. Chapters examine adult language, first and second language acquisition, and the motivations behind historical change.